2022
DOI: 10.1002/eap.2531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stand structure and ungulates on understory vegetation in managed and unmanaged forests

Abstract: Conventional conservation policies in Europe notably rely on the passive restoration of natural forest dynamics by setting aside forest areas to preserve forest biodiversity. However, since forest reserves cover only a small proportion of the territory, conservation policies also require complementary conservation efforts in managed forests in order to achieve the biodiversity targets set up in the Convention on Biological Diversity. Conservation measures also raise the question of large herbivore management i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
2
5
0
Order By: Relevance
“…5, and Supplementary Tables 38, 39) by selectively feeding on more palatable species, thereby freeing up physical space. This is consistent with studies showing that herbivory favors low-stature herbs in the absence of eutrophication, many of which have lower N-demands 15,71 . Conversely, under elevated N-levels, selective feeding may not suffice to control N-demanding species, as these may be too strongly promoted by the convergent increase in N, light and disturbance.…”
Section: Discussionsupporting
confidence: 91%
“…5, and Supplementary Tables 38, 39) by selectively feeding on more palatable species, thereby freeing up physical space. This is consistent with studies showing that herbivory favors low-stature herbs in the absence of eutrophication, many of which have lower N-demands 15,71 . Conversely, under elevated N-levels, selective feeding may not suffice to control N-demanding species, as these may be too strongly promoted by the convergent increase in N, light and disturbance.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, sites with low N-deposition showed increases in small-ranged and threatened species, with concomitant declines in non-native, nutrient-demanding species as herbivory increased. This finding echoes studies showing that without eutrophication, herbivory favors low-stature, lightdemanding herbs, many of which have lower N-demands 15,69 . This pattern may reflect how herbivores tend to feed on palatable species with high leaf N and reduced toxicity and perhaps that these species cannot recover as readily from herbivory when N is limited 70 .…”
Section: Discussionsupporting
confidence: 78%
“…In the short term, reductions in canopy closure enhance the establishment of light-demanding species [83], but species composition changes when tall shrubs and saplings become dominant [84]. However, the effect of canopy openings on understory attributes depends on the functional group considered, e.g., bryophytes or vascular plants [85,86], and it is contingent on human activities and site conditions [40,[85][86][87]. In this study, we did not consider understory diversity directly, but we observed a higher presence of B. sempervirens in the understory of forests showing dieback (Table 1, Figure 5).…”
Section: Discussionmentioning
confidence: 99%